2018
DOI: 10.1016/j.earscirev.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The Late Cretaceous Western Interior Seaway as a model for oxygenation change in epicontinental restricted basins

Abstract: Deoxygenation is a critical problem facing the ocean as the world warms, and has the potential to effect coastal upwelling zones, shelf areas influenced by high runoff and nutrification, and restricted and semi-restricted basins. The mechanisms that drive deoxygenation in these diverse environments are still not fully understood, in part because the modern record of redox change is short and anoxia is still relatively rare in the modern ocean. Here, we address this problem of scale by studying deoxygenation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 103 publications
(183 reference statements)
2
37
2
Order By: Relevance
“…Seven sites document anoxic conditions before OAE2. They are located in the Southern Central Atlantic and in the Gulf of Mexico (Figure 10; Kuypers et al., 2002; Lowery, Cunningham, et al., 2017; Lowery, Leckie, et al., 2017; Owens et al., 2012; Perez‐Infante et al., 1996; van Helmond, Ruvalcaba Baroni, et al., 2014; Westermann et al., 2014). In particular, previous studies suggested that the anoxic area surrounding the Equatorial Atlantic Gateway was driven by the estuarine circulation established between the Pacific and Central Atlantic (Topper et al., 2011; Trabucho Alexandre et al., 2010) but our results demonstrate that this anoxic area is stable even in the ShallowCAS simulation despite the disappearance of the estuarine circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Seven sites document anoxic conditions before OAE2. They are located in the Southern Central Atlantic and in the Gulf of Mexico (Figure 10; Kuypers et al., 2002; Lowery, Cunningham, et al., 2017; Lowery, Leckie, et al., 2017; Owens et al., 2012; Perez‐Infante et al., 1996; van Helmond, Ruvalcaba Baroni, et al., 2014; Westermann et al., 2014). In particular, previous studies suggested that the anoxic area surrounding the Equatorial Atlantic Gateway was driven by the estuarine circulation established between the Pacific and Central Atlantic (Topper et al., 2011; Trabucho Alexandre et al., 2010) but our results demonstrate that this anoxic area is stable even in the ShallowCAS simulation despite the disappearance of the estuarine circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The once delta plain shifted to a distal floodplain with the continued development of the fluvial complex and adjacent floodplain fines preserved in slightly more arid climatic conditions ( Roybal, 1982 ; Campbell, 1984 ; Hoffman, 1996 ; this study). In a broader context, with the newly interpreted MDAs for the Moreno Hill, emplacement of sediment into the depo-center would have initiated during the latest phase of the Greenhorn continuing through the Frontier-Ferron regression (Mancos Seaway) ( Kauffman, 1984 , Blakey, 2014 ; Lowery et al, 2018 , Fig. 4, p. 14; Miall & Catuneanu, 2019 ; and references therein).…”
Section: Discussionmentioning
confidence: 98%
“…WIS marine faunas are generally more depauperate than other Cretaceous faunas due to the basin's restricted circulation, brackish surface waters, dysoxic benthos, and episodic connection between the northern and southern regions, which would restrict dispersal (Jeletzky 1970; Hay et al 1993; Lowery et al 2018). An even smaller pool of species with the physiological tolerances necessary to colonize Black Hills seep habitats would have been present in the WIS; for example, tolerance of sulfide is important for colonization of shallow seeps (Dando 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stress from seep-fluid composition, the restricted circulation and low-oxygen conditions common in the WIS could be an additional stressor leading to more homogeneous assemblages (Jeletzky 1970; Wright 1987; Hay et al 1993; Lowery et al 2018). Well-developed oxygen minimum zones in the modern ocean tend to homogenize faunal assemblages (Levin et al 2000a); thus the low-heterogeneity of the Black Hills seeps may instead reflect lower-oxygen conditions during their formation.…”
Section: Discussionmentioning
confidence: 99%